Croatian Ethnology on Intangible Heritage - Petrović Leš, Tihana (2009)
This paper aimes at showing the ways in which the research of ethnologists from different institutions during the 20th and the 21st century resulted in rich documentation on intangible cultural heritage, which is today invaluable for the future researches, but also serves as the basis for its revitalization. The results of the continual collecting and research as well as the publications and exhibitions, today provide the basis for expert evaluations for legislative protection of intangible heritage, as well as for the guidelines for its preservation. Furthermore, current ethnological researches monitor the changes and the ways in which heritage has been included in the presentation of local communities in contemporary social contexts.